Eros y Tanatos: representación de la melancolía en Ophelia - Rodríguez Vásquez, Erika (2019)
The main purpose of this article is to discuss the representation of melancholy, as a result of the tension between the erotic and the morbid in the poetry book Ophelia. This predominantly melancholic feeling in the book verses will be analyzed taking into account the correspondence between two axes: eros and tanatos, as foundations in the perception of a catastrophic tone and the mythical character of the Ofelian character. In this sense, emphasis will be placed on demonstrating the presence of a discourse and tone within the framework ofthe creation and spirit of the end of the century.